Changes In Tourism After the Covid-19 Pandemic: Results of Qualitative Research - Iryna MANCZAK; Izabela GRUSZKA; Marta DROZDOWSKA (Communications of International Proceedings, 2022)
The purpose of this paper is to identify post-pandemic COVID-19 changes in tourism. For the purposes of the study a qualitative approach was taken. The article presents the results of virtual interviews conducted with representatives of selected entities operating in tourism in Lower Silesia and Lesser Poland. The obtained research material was used to indicate tourist phenomena that will be characteristic in the near future. The certain amount of attention was also paid to the directions of development of inter-organizational cooperation in the opinion of research participants. This article overviews the literature concerning the impact of the Covid-19 pandemic on tourism. The key part of the presented considerations lies in an outline of the applied research approach, including a discussion of the obtained results. On the basis of the aforementioned discussion, answers to the research questions were formulated.
Keywords: Tourism; Covid-19 Pandemic; Qualitative Research; Virtual Interviews.